2015
DOI: 10.1177/1470320315576256
|View full text |Cite
|
Sign up to set email alerts
|

Activation of renin–angiotensin–aldosterone system (RAAS) in the lung of smoking-induced pulmonary arterial hypertension (PAH) rats

Abstract: Objectives: To explore the role of the renin-angiotensin-aldosterone system (RAAS) in the pathogenesis of pulmonary arterial hypertension (PAH) induced by chronic exposure to cigarette smoke. Methods: 48 healthy male SD rats were randomly divided into four groups (12/group): control group (group A); inhibitor alone group (group B); cigarette induction group (group C); cigarette induction + inhibitor group (group D). After the establishment of smoking-induced PAH rat model, the right ventricular systolic pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 22 publications
3
56
0
1
Order By: Relevance
“…In our model, we found elevated lung concentrations of Ang II in aged female PSGL‐1 −/− mice. Thus, hypoxic and monocrotaline‐treated rats showed increased Ang II and AT 1 R levels , and patients with PAH showed higher levels of pulmonary Ang II due to increased activity of ACE, as well as increased expression and signaling of AT 1 R, resulting in augmented vascular smooth muscle cell (VSMC) proliferation . Inhibitors of the renin–angiotensin–aldosterone system (RAAS) have been shown to have an effect in reducing PAP and other PAH signs in some animal models and in pilot studies with small patient cohorts, highlighting the role of RAAS in the pathology of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, we found elevated lung concentrations of Ang II in aged female PSGL‐1 −/− mice. Thus, hypoxic and monocrotaline‐treated rats showed increased Ang II and AT 1 R levels , and patients with PAH showed higher levels of pulmonary Ang II due to increased activity of ACE, as well as increased expression and signaling of AT 1 R, resulting in augmented vascular smooth muscle cell (VSMC) proliferation . Inhibitors of the renin–angiotensin–aldosterone system (RAAS) have been shown to have an effect in reducing PAP and other PAH signs in some animal models and in pilot studies with small patient cohorts, highlighting the role of RAAS in the pathology of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…The arteriole expression of ACE is consistent with the hypothesis that locally increased production of ANG II contributes to the process of pulmonary vascular remodeling in PAH. In chronic cigarette smoke-induced PAH in rats, ANG II level in the lung was increased with increased expression of ACE and decreased expression of ACE2 (60,148). The decreased expression of ACE2 in pulmonary artery smooth muscle cells from cigarette smoke-exposed rats correlated with increased proliferation (60).…”
Section: Nicotine and The Ras In The Lungmentioning
confidence: 94%
“…The decreased expression of ACE2 in pulmonary artery smooth muscle cells from cigarette smoke-exposed rats correlated with increased proliferation (60). In addition, losartan administration in vivo reduced ANG II level in the lung, restored ACE2 expression, and ameliorated pulmonary vascular remodeling and smoke-induced increase in right ventricular systolic pressure (60,148). Koka et al (81) showed that ANG II downregulates ACE2 via AT 1 R-mediated extracellular signal-regulated kinase (ERK)/p38 MAPK signaling pathways; thus the decreased ACE2 expression by chronic cigarette smoke exposure could be mediated by a mechanism dependent on ANG II and AT 1 R. Cigarette smoke exposure in mice also increases ACE expression in the lung, and this upregulation was greater in ACE2 knockout mice compared with the wild-type controls (69).…”
Section: Nicotine and The Ras In The Lungmentioning
confidence: 97%
“…A growing body of work has focused on the importance of ACE2 in PAH and associated right HF. Decreased lung ACE2 expression 79,80 and enzymatic activity 81 , along with increased circulating Ang II levels 82 , have been observed in PAH. Additionally, reduction in circulating ACE2 and Ang-(1-7) levels has been observed in patients with PAH from congenital HD 83,84 .…”
Section: Ace2 In Pulmonary Arterial Hypertensionmentioning
confidence: 99%